Effects of Soil Parent Material and Climate on the Performance of Vitis vinifera L. cvs. Sauvignon blanc and Cabernet Sauvignon - Part II. Climate, Leaf Analysis, Juice Analysis and Wine Quality - Shange, L.P.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
A five-year investigation (2004/05 to 2008/09) was carried out in two Sauvignon blanc and two Cabernet Sauvignon vineyards in the Helderberg area, Western Cape, South Africa. Soils, derived mainly from granite and shale, were identified in each vineyard. Climatic parameters were measured, while leaves and juice were analysed. Experimental wines were prepared and evaluated annually. The nutritional status of the leaf blades and petioles was not affected by soil parent materials in a consistent pattern. Juice N of grapevines on the shale-derived soil was usually higher than that of vines on the granite-derived soil. The effect of soil parent material on Sauvignon blanc wine style appeared to have been more distinct at the locality where wine quality was highest. At this locality, wine from the grapevines on shale-derived soil (higher water-holding capacity) was best in 2004/05 (dry season), while the reverse was true in the 2007/08 season (wet). The style and/or quality of Cabernet Sauvignon wines were affected to a greater extent by differences in soil parent materials, relative to Sauvignon blanc. Differences were especially noticeable during the cooler and wetter seasons. Better drainage in the case of the granite-derived soils, due to the higher coarse sand fraction, may have played a positive role during these seasons.